(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Premessa - 2. Reformatio in capite et membris - 3. La riforma gregoriana - 4. Rinnovamento monastico e nuove forme di religiosità - 5. Erasmo da Rotterdam e l’Umanesimo cristiano - 6. Ecclesia semper reformanda - 7. Gli antecedenti della Riforma - 8. I poveri di Lione - 9. Il movimento dei Lollardi - 10. La rivoluzione boema - 11. Le guerre hussite. The Protestant Reformation between requests for renewal and heretical movements ABSTRACT: The Protestant Reformation represents an epochal event as it is widely considered the true moment of transition from the Middle Ages to the modern age. Without wishing in the least to diminish the innovative significance of the aforementioned phenomenon, it is however necessary to point out how the Catholic Church, during the course of its history, has been crossed by a yearning for regeneration that has involved both the constitutional and the devotional aspects of its being. To this end, it is enough to recall the reforming work of Gregory VII, the Cluniac monastic rigor, the contribution of some regular Orders (mendicants), as well as the spread of new forms of religiosity, from the modern Devotio to the Christian humanism of Desiderio Erasmus of Rotterdam. Similarly, the originality of the Reformation did not prevent modern Protestant historiography from considering it the natural result of an evangelical pluralism already present in the twelfth century. The direct reference is to the doctrines of Pietro Valdo, John Wycliff and Jan Hus, and in particular to their ecclesiology which in various ways will be proposed by Martin Luther, with his own peculiarity, and without ever reducing himself to it.